IMPLEMENTATION OF THE K-MEANS ALGORITHM IN DETERMINING THE MAJOR OF HIGH SCHOOL STUDENTS - Rahayu Mayang Sari (Sean Institute, 2022)
This pre-school entrance examination is conducted to determine the abilities and scores of students to determine the major to be taken while in high school. In The State High School (SMA) 3 Payakumbuh has 2 majors, namely Natural Sciences (IPA) and Social Sciences (IPS). The determination of this major is carried out since the student is in class X. Therefore, the school needs a way to group the results of students' test scores. This study discusses the application of data mining using the k-means algorithm with the implementation using the Tanagra application. Where in inputting the data, the student's name is needed, the number of questions answered and the total score. Where later the scores are grouped into two, the highest score and the lowest score, the highest score makes students enter the natural science (IPA) department group and the lowest score makes students enter the Social Sciences (IPS) department group